Bioinspired diphenylalanine with aggregation-induced emission in deep ultraviolet range. (1st February 2016) - Gan, Zhixing; Meng, Ming; Di, Yunsong; Huang, Shisong
Abstract : Diphenylalanine showing aggregation-induced emission (AIE) at 282 nm is demonstrated. The luminescent intensity increases rapidly with the occurrence of aggregation. Time-resolved and temperature-dependent PL spectra are used to interpret the AIE effect. Abstract : Luminophores with aggregation-induced emission (AIE) in the deep ultraviolet are still quite lacking, albeit with plenty of luminogenic molecules showing a pronounced AIE effect. In this communication, the bioinspired diphenylalanine with AIE at 282 nm is reported. Photoluminescence (PL) intensity of this molecule increases rapidly with occurrence of aggregation. Furthermore, time-resolved and temperature-dependent PL spectra reveal the AIE phenomenon derives from the restriction of intramolecular motions.